Physiological quality of zucchini seeds is positively affected by postharvest resting periods - Aguilar, Ariel Santivanez [UNESP] (2024)
This study evaluates zucchini, Cucurbita pepo, , seed quality after postharvest resting periods. Zucchini fruits harvested 63 days after transplanting were maintained for 0, 3, 6, 9, or 12 days before seed extraction. The percent of processed seeds (clean and whole seeds), the weight of 100 seeds, germination, first count in germination, germination speed index, electrical conductivity, nitrogen (N), and protein contents were evaluated. The weight of 100 seeds, percent of processed seeds, germination, vigor, seed N, and protein content increased as the resting period after harvest (days) increased. Seed electrical conductivity decreased as days of postharvest rest increased. After the harvest of the zucchini fruits, the resting period positively affected the production of homogeneous and high-quality zucchini seeds. Thus, the Cucurbitaceae plant family, such as zucchini, will benefit from storage or resting after fruit harvest, enabling the seeds to complete their maturation process, reaching maximum germination and vigor. The definition of the resting periods allows early fruit harvestings, reducing seed exposure to weathering and biotic stresses (e.g., microorganisms and insect pests) and improving the area's agronomic uses.